2017
DOI: 10.1177/2047487317729538
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy is associated with health behaviour and self-reported health: A large population-based study in individuals with cardiovascular disease

Abstract: BackgroundHealth literacy may constitute a modifiable determinant of health behaviour and affect cardiovascular disease prevention. This study investigates the associations between health literacy and health behaviour as well as health status.DesignA cross-sectional study on a population-based sample of people with acute myocardial infarction, angina pectoris or stroke (N = 3116).MethodsHealth literacy was assessed using two dimensions from the Health Literacy Questionnaire: ‘understanding health information’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
202
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(244 citation statements)
references
References 42 publications
29
202
1
12
Order By: Relevance
“…A high level of health literacy skills has been associated with health-promoting behaviours and better health outcomes in relation to self-reported health status, dietary habits, physical activity, smoking, alcohol consumption, and glycaemic control of diabetes [47][48][49]. We found that lower This is a large Danish prospective cohort study among outpatients with epilepsy in which register data from all the included participants were used.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of health literacy skills has been associated with health-promoting behaviours and better health outcomes in relation to self-reported health status, dietary habits, physical activity, smoking, alcohol consumption, and glycaemic control of diabetes [47][48][49]. We found that lower This is a large Danish prospective cohort study among outpatients with epilepsy in which register data from all the included participants were used.…”
Section: Discussionmentioning
confidence: 99%
“…Health promotion, as reflected in a healthy lifestyle, is an integral part of disease prevention [4,5]. Health-promoting behaviour has been associated not only with improved physical and mental health outcomes [6][7][8][9], but also with lower healthcare costs [10].…”
Section: Introductionmentioning
confidence: 99%
“…13 A large and comprehensive analysis of the relationship between health literacy and health behaviour has shown significant associations between health literacy and increased physical activity, healthier diet and higher self-reported health status, better weight control, and abstinence from smoking, in individuals with CV disease. 14 …”
Section: Health Literacymentioning
confidence: 99%